PENDIDIKAN KARAKTER DI PONDOK PESANTREN ANAK-ANAK - M Yusuf Agung Subekti (Ta`Limuna: Jurnal Pendidikan Islam, 2015)
In general, the pesantren boarding school specializing handle prioritize the education of children to read and write the Koran, which is the core element kiai, Mrs. housekeeper, teacher council, students, mosque, hostel, and learning curriculum Koran has become a sub-culture of its own. Because of the character education very early age how urgent it is to form a sub-culture of personal private life tough face reality era of modernization and globalization. In addition, many stakeholders stated that schools are educational institutions that can serve as a model character education in Indonesia. Two questions will be addressed in this paper is how the strategy and the pattern of character education implemented by schools to form a sub-culture and how the shape of the sub-culture. This study focuses attention on Nur Mamba'ul Hisan Satreyan Kanigoro Blitar.